The Influence of Managerial Values on Corporate Social Performance of SMEs in the UK: A Moderated Mediation Analysis - Alsyoof, Sarah Mohamamd Suleiman (Decision Making: Applications in Management and Engineering, 2024)
Research on the micro-foundations of corporate social performance (CSP) in small and medium-sized enterprises (SMEs) is limited. Building on upper echelons, stakeholders, and Schwartz value theories, this paper aims to investigate the influence of managerial values on SMEs’ CSP with the mediating role of managers’ CSR orientation (CSRO). The study also explores how managerial experience and educational levels moderate the mediating effects of CSRO. The study was conducted on a sample of 248 top managers from SMEs in the UK using path analysis, regression analysis, mediation analysis, and moderated mediation analysis. The findings indicate that only self-transcendence and openness to change values significantly positively affect CSP, while self-enhancement and conservation values do not. In addition, philanthropic CSRO mediates the relationship between self-transcendence values and CSP, while none of the CSRO constructs mediate the openness to change-CSP relationship. For highly experienced managers, all value dimensions influence CSP significantly, with self-transcendence being mediated by philanthropic and legal CSROs. For master’s graduates, self-enhancement positively impacts CSP, partly through economic CSRO. Openness to change positively affects CSP directly, without CSRO mediation. For PhD managers, only conservation values significantly impact CSP without the mediation role of CSRO. This study presents a novel moderated mediation model that analyzes the relationship between managers’ values and CSP, using CSRO as a mediator and managers’ experience and education level as moderators. Not only does this paper provide in-depth insights into personal CSP drivers in SMEs, but it also enlightens managers and education policymakers about the necessity of matching personal values with CSR concerns.